PENERAPAN NILAI-NILAI KEARIFAN LOKAL DALAM KEHIDUPAN MASYARAKAT DESA GANDON DI ERA GLOBALISASI GUNA MENDUKUNG KETAHANAN WILAYAH - Rita Kuntarti; Dwi Joko Siswanto (JURNAL MAHATVAVIRYA, 2022)
Local wisdom is the attitude, view and ability of a community in managing its spiritual and physical environment, which gives the community the endurance and power to grow in the area where the community is located. In other words, local wisdom is a creative answer to local geographic-geopolitical, historical and situational situations. Along with these developments, competition in various fields is also getting higher due to the swift flow of service capital to all corners of the world which affects national integrity, all of which only possible with the quality of competence that is highly competitive. Globalization is a concept that is widely used to respond to world conditions that are without boundaries or barriers. One of the realities that must always be criticized to respond to globalization is that globalization has actually eroded and even killed the local wisdom values ​​of a region. With qualitative methods, this study aims to determine the application, preservation and local wisdom that exists and is carried out by the residents of Gandon Village in the current era of globalization. In addition, whether local wisdom in Gandon Village can support the resilience of the local area. Through this research, it can be concluded that local wisdom in Gandon Village is not eroded by the presence of globalization and in fact supports regional resilience.